Whole-body bioluminescence imaging of T-cell response in PDAC models - McMorrow, Roisin; Zambito, Giorgia; Nigg, Alex; Lila, Karishma; van den Bosch, Thierry P. P.; Lowik, Clemens W. G. M.; Mezzanotte, Laura (Frontiers in Immunology, 2023)
The location of T-cells during tumor progression and treatment provides crucial information in predicting the response in vivo. Here, we investigated, using our bioluminescent, dual color, T-cell reporter mouse, termed TbiLuc, T-cell location and function during murine PDAC tumor growth and checkpoint blockade treatment with anti-PD-1 and anti-CTLA-4. Using this model, we could visualize T-cell location and function in the tumor and the surrounding tumor microenvironment longitudinally. We used murine PDAC clones that formed in vivo tumors with either high T-cell infiltration (immunologically ‘hot’) or low T-cell infiltration (immunologically ‘cold’). Differences in total T-cell bioluminescence could be seen between the ‘hot’ and ‘cold’ tumors in the TbiLuc mice. During checkpoint blockade treatment we could see in the tumor draining lymph nodes an increase in bioluminescence on day 7 after treatment. In the current work, we showed that the TbiLuc mice can be used to monitor T-cell location and function during tumor growth and treatment.